The Desired Managerial Leader Behavior: Leader Profile in the Education Sector in Iceland Examined From a Follower-Centric Perspective - Lolita Urboniene; Erla S. Kristjánsdóttir; Inga Minelgaite; Romie F. Littrell (SAGE Open, 2018)
This article presents a study of desired leadership behavior in the educational sector in Iceland. This sector has been undergoing major challenges during recent years, including restructuring and mergers of schools, strikes of teachers’ professional unions, and increasing dropout rates. This situation requires exceptional leadership together with the understanding that leadership is a culture and context contingent phenomenon. However, research on managerial leadership in the education sector in Iceland is virtually nonexistent, presenting a gap in literature as well as failure to contribute to solving issues in practice. This article contributes to closing this gap by investigating the desired leader profile from a follower-centric perspective. The results indicate that the most desired leader behaviors in this sector tend to be relationship orientated, suggesting a need to focus on the “soft” side of leadership and reconsider overemphasis on bureaucracy. Effects of gender and demographic differences are minimal, suggesting coherence with structural theory. Managerial leadership implications and future research directions are discussed.